Cr(III)aq separation by flotation with multipolar collector. Issue 2 (22nd January 2020) - Craioveanu, Maria Graţiela; Stoica, Ligia; Constantin, Carolina; Oprea, Ovidiu
ABSTRACT: This paper focuses on the separation of Cr(III)aq by ion and precipitate flotation using a multipolar collector, caffeic acid. The optimum separation parameters were established and were verified on real wastewater samples. The complexation function of CA with Cr(III) ions was studied. The obtained results suggested that, at pH≅6.0 and [CA]:[Cr(III)] = 1.25:1 molar ratio, a chelate compound with the involvement of phenolic hydroxyl groups, Na[Cr(H2 O)3 (OH)CA], most likely is formed, and at pH≅7.5 and [CA]:[Cr(III)] = 0.01:1 molar ratio, a mixture of Cr(III) hydroxo aqua species and caffeate is formed. The high separation efficiencies (R > 98%) support the possibility of using CA as collector reagent.